Foraging behaviour and health status of Red-billed Oxpeckers (Buphagus erythrorhynchus) in the Kruger National Park, South Africa - Botes, Mariska (University of the Free State, 2019)
Red-billed Oxpeckers (Buphagus erythrorhynchus) are tick feeding birds that reduce ectoparasite loads on African ungulates. However, little is known about their feeding ecology, seasonal abundance and health wellbeing. All these attributes contribute towards their conservation. I studied the Red-billed Oxpecker feeding ecology and health status in the southern regions of Kruger National Park by documenting their seasonal abundance, infection prevalence, body condition and foraging behaviour (host preference and foraging location on host). No significant difference in Oxpecker abundance was observed between the three seasons. Nine potential ungulate host species were recorded and birds were observed feeding on eight of the present species. White rhinoceros (Ceratotherium simum), Cape buffalo (Syncerus caffer) and giraffe (Giraffa camelopardalis) were the most preferred hosts whereas waterbuck (Kobus ellipsiprymnus) were the least preferred host. Birds preferred sitting and foraging from the back, head and neck of the host ungulate – where they appeared more tolerated by the host. No wound feeding activity was recorded during this study. In total, 30 Red-billed Oxpeckers were caught and blood and feather samples from them were screened for parasites. Ectoparasite prevalence on birds was highest during the summer months, with the majority found on the flight wing feathers. It was found that birds with ectoparasites seemed to have a lower body condition index compared to those with no ectoparasites. The most common Haemoparasites found in the Oxpeckers were Leucocytozoon. It was also the only haemoparasite found during the dry season.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2019
Keywords: Red-billed Oxpeckers; Buphagus erythrorhynchus; Kruger National Park; Feeding ecology; Health status; Seasonal abundance; Infection prevalence; Body condition; Foraging behaviour